2014
DOI: 10.1071/ch13438
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient One-pot Two-component Protocol for Regio- and Chemoselective Synthesis of 5-Aryloyl-1,3,7,9-tetraalkyl-2,8-dithioxo-2,3,8,9-tetrahydro-1H-pyrano[2,3-d:6,5-d′]dipyrimidine-4,6(5H,7H)-diones

Abstract: Novel symmetric fused pyrano [2,3-d]pyrimidine derivatives were synthesized in 75-92 % yield by a one-pot twocomponent reaction of arylglyoxals and 1,3-dialkyl-2-thiobarbituric acids in ethanol at room temperature. This is the first protocol to be reported for the synthesis of 5-aryloyl-1,3,7,9-tetraalkyl-2,8-dithioxo-2,3,8,9-tetrahydro-1H-pyrano [2,3-d:6,5-d 0 ]dipyrimidine-4,6(5H,7H)-diones and the significant features of the present protocol are simplicity, high yields, a simple isolation procedure, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…These precipitates were isolated and recrystallized in methanol. Our aim from adding ammonium acetate to the reaction mixture was the synthesis of pyrrolopyrimidine derivatives but considering 1 H-nmr spectra of all products showed that similar to our previously synthesized dialkyl substituted pyrano [2,3-d]pyrimidines, 20 there is a singlet in the average chemical shift 5.5 ppm which relates to CH of pyran ring. Namely, ammonium acetate instead of addition on carbonyl groups of 1,4-dicarbonyl intermediate acts as catalyst in these reactions and it helps to close pyran system on the pyrimidinone rings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These precipitates were isolated and recrystallized in methanol. Our aim from adding ammonium acetate to the reaction mixture was the synthesis of pyrrolopyrimidine derivatives but considering 1 H-nmr spectra of all products showed that similar to our previously synthesized dialkyl substituted pyrano [2,3-d]pyrimidines, 20 there is a singlet in the average chemical shift 5.5 ppm which relates to CH of pyran ring. Namely, ammonium acetate instead of addition on carbonyl groups of 1,4-dicarbonyl intermediate acts as catalyst in these reactions and it helps to close pyran system on the pyrimidinone rings.…”
Section: Resultsmentioning
confidence: 99%
“…Following to our recent work on the synthesis of new substituted pyranopyrimidines, 20 we found that unlike 1,3-diethyl and 1,3-dimethylthiobarbituric acids, stirring the mixture of barbituric acid or thiobarbituric acid and arylglyoxalmonohydrates in ethanol in both room temperature and reflux conditions in order to synthesis of the corresponding 5-aryloyl substituted pyrano [2,3-d]pyrimidines was failed which this phenomenon may be because of poor solublity of barbituric acid and thiobarbituric acid in ethanol. Therefore, we changed the reaction solvent to water as a suitable solvent for barbituric acid derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to pyridine has harmful effects on the liver, kidneys, immune systems and reproductive functions, and has potential carcinogenicity. [27][28][29][30][31] Following to recent reports about the application of arylglyoxals (AG) in heterocyclic chemistry, 26,[32][33][34][35][36][37][38][39][40] herein we have applied ZrOCl2•8H2O as recyclable, non-toxic and green catalyst for the regioselective synthesis of 3-arylpyrimido [4,5-c] We also studied the influence of the amount of ZrOCl2•8H2O on the reaction yields. We found that the best yield is obtained when we used the ZrOCl2•8H2O 20 mol% as a catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Rimaz et al 192 developed the chemo- and regioselective synthesis of a novel symmetric fused 158a through the reaction of arylglyoxal 157 (1 mmol) with 11a / 11b (1 mmol) in absolute alcohol (10 mL) at room temperature for appropriate hours ( Scheme 106 ). The enol form 158a was stable only in solution phase and all the compounds were gained in keto form 158 .…”
Section: Synthesis Of 5-aryl-substituted Pyrano[23- D ...mentioning
confidence: 99%